Post-earthquake field measurement-based system identification and finite element modeling of an 18-story masonry-infilled RC building - Mohammed, Mohammed A. (2019)
This paper describes the system identification and finite element modeling of an 18-story unreinforced masonry infilled reinforced concrete building that was damaged following the 2015 M7.8 Gorkha Earthquake, Nepal, and subsequent aftershocks. The identification is performed using the ambient vibration data collected using broadband seismometers and accelerometers. The new apartment building was seismically designed using Indian Codes and Standards. At the time of the earthquake mainshock, its construction was complete as the building was being finalized for handover to the clients. Following the earthquake mainshock and aftershocks, most of the damage to the building was observed in the non-structural masonry infill walls, while minor damage was observed in the diaphragms and elevator core link beams on lower stories. The ambient vibration response of the damaged building was recorded using either: (1) fifteen accelerometers at different setups, or (2) three seismometers. The dynamic characteristics of interest are the modal parameters of the first few lateral and torsional vibration modes. The modal identification results from the two measurement systems are compared to provide insight into the uncertainty of the results. In addition, two finite element models of the structure are developed from the information provided in the design documentation of the building. The models are tuned to match the identified modal parameters and compared with each other. Special attention is placed on the stiffness of structural and non-structural elements.